Partnership and Participation—A Social Network Analysis of the 2017 Global Fund Application Process in the Democratic Republic of the Congo and Uganda. Issue 1 (5th November 2020) - Shelley, Katharine D.; Kamya, Carol; Mpanya, Godefroid; Mulongo, Salva; Nagasha, Shakilah N.; Beylerian, Emily; Duber, Herbert C.; Hernandez, Bernardo; Osterman, Allison; Phillips, David E.; Shearer, Jessica C.; ,
Background: The Global Fund to Fight AIDS, Tuberculosis and Malaria was founded in 2002 as a public-private partnership between governments, the private sector, civil society, and populations affected by the three diseases. A key principle of the Global Fund is country ownership in accessing funding through "engagement of in-country stakeholders, including key and vulnerable populations, communities, and civil society." Research documenting whether diverse stakeholders are actually engaged and on how stakeholder engagement affects processes and outcomes of grant applications is limited. Objective: To examine representation during the 2017 Global Fund application process in the Democratic Republic of the Congo (DRC) and Uganda and the benefits and drawbacks of partnership to the process. Methods: We developed a mixed-methods social network survey to measure network structure and assess perceptions of how working together in partnership with other individuals/organizations affected perceived effectiveness, efficiency, and country ownership of the application process. Surveys were administered from December 2017–May 2018, initially to a set of central actors, followed by any individuals named during the surveys (up to 10) as collaborators. Network analyses were conducted using R. Findings: Collaborators spanning many organizations and expertise areas contributed to the 2017 applications (DRC: 152 nodes, 237 ties; Uganda: 118 nodes, 241 ties). Participation from NGOs and civil society representatives was relatively strong, with most of their ties being to different organization types, Uganda (63%), and DRC (67%), highlighting their collaborative efforts across the network. Overall, the perceived benefits of partnership were high, including very strong ratings for effectiveness in both countries. Perceived drawbacks of partnership were minimal; however, less than half of respondents thought partnership helped reduce transaction costs or financial costs, suggesting an inclusive and participatory process may come with short-term efficiency tradeoffs. Conclusions: Social network analysis can be useful for identifying who is included and excluded from the process, which can support efforts to ensure stronger, more meaningful engagement in future Global Fund application processes.